2011
DOI: 10.1371/journal.pone.0024402
|View full text |Cite
|
Sign up to set email alerts
|

Host Transcription Factors in the Immediate Pro-Inflammatory Response to the Parasitic Mite Psoroptes ovis

Abstract: BackgroundSheep scab, caused by infestation with the ectoparasitic mite Psoroptes ovis, results in the rapid development of cutaneous inflammation and leads to the crusted skin lesions characteristic of the disease. We described previously the global host transcriptional response to infestation with P. ovis, elucidating elements of the inflammatory processes which lead to the development of a rapid and profound immune response. However, the mechanisms by which this response is instigated remain unclear. To ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Several genes, such as fos , nr4a1 , dusp1 , and nfkbia , which increased after acupuncture needling and are part of the immediate early genes, 6 respond to various external stimulations and trigger the expression of stress response genes. Among them, nfkbia is categorized in the B and T cell receptor pathways and is involved in local immunomodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes, such as fos , nr4a1 , dusp1 , and nfkbia , which increased after acupuncture needling and are part of the immediate early genes, 6 respond to various external stimulations and trigger the expression of stress response genes. Among them, nfkbia is categorized in the B and T cell receptor pathways and is involved in local immunomodulation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, microscopic examination of the skin from infested ruminants reveals an increased dermal thickness and a superficial, perivascular dermatitis characterised by a fast influx of lymphocytes (including γδ T-cells in sheep), macrophages, mast cells, neutrophils and eosinophils [ 9 – 12 ]. Previous work on sheep scab demonstrated an up-regulation of genes encoding for pro-inflammatory and pro-allergic mediators [interleukin (IL)-1, IL-8, IL-6] and molecules involved in extravasation of immune cells [ 13 , 14 ]. Several infectious diseases, including scabies, have been linked to CD4+ T-helper cell (Th) differentiation into specific Th1, Th2, Th17 or regulatory (Treg) lineages [ 15 ] and the pro-inflammatory response in the skin of P. ovis infested sheep evolves towards a Th2 immune response within 24 h after infection [ 13 , 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on sheep scab demonstrated an up-regulation of genes encoding for pro-inflammatory and pro-allergic mediators [interleukin (IL)-1, IL-8, IL-6] and molecules involved in extravasation of immune cells [ 13 , 14 ]. Several infectious diseases, including scabies, have been linked to CD4+ T-helper cell (Th) differentiation into specific Th1, Th2, Th17 or regulatory (Treg) lineages [ 15 ] and the pro-inflammatory response in the skin of P. ovis infested sheep evolves towards a Th2 immune response within 24 h after infection [ 13 , 14 , 16 ]. A similar pattern has been described in Sarcoptes scabiei infested mice and dogs with transcription of Th2 like cytokine profiles in lymph node cells and PBMC respectively [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, NJ analysis revealed that PsoSP1 yielded a close relationship with Der f 27. In combination with the homology and the genetic relationship between Pso SP1 and Der f 27, PsoSP1 may be considered as an allergen of P. ovis, which was possibly associated with the instigation of the host cutaneous pro-in ammatory response [23]. Additionally, this cutaneous in ammation resulted in serum extravasation to provide su cient food for mites population growth and cause aggravation of scabby lesions [7,24].…”
Section: Discussionmentioning
confidence: 99%